2004
DOI: 10.1016/j.apsusc.2004.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen deficiency on electronic properties of AlGaN surfaces subjected to thermal and plasma processes

Abstract: Effects of device processing on chemical and electronic properties of AlGaN surfaces were investigated. The X-ray photoelectron spectroscopy analysis showed serious deterioration such as stoichiometry disorder and nitrogen deficiency (N deficiency) at the AlGaN surfaces processed by high-temperature annealing, H 2 -plasma cleaning, dry etching in CH 4 /H 2 /Ar plasma and deposition of SiO 2 . This resulted in high density of surface states at the processed AlGaN surface. Furthermore, the N deficiency introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 41 publications
(61 reference statements)
6
89
1
3
Order By: Relevance
“…A mixed layer, in which GaN, Ga, Al, Ni, and O coexisted, indicates that group-III oxides possibly formed as well. Group-III oxides such as GaO x and AlO x may leave group-III (Ga or Al) vacancies [15] as deep states. The reaction process of Ni and O in the AlGaN barrier may be related to the formation of deep states.…”
Section: Resultsmentioning
confidence: 99%
“…A mixed layer, in which GaN, Ga, Al, Ni, and O coexisted, indicates that group-III oxides possibly formed as well. Group-III oxides such as GaO x and AlO x may leave group-III (Ga or Al) vacancies [15] as deep states. The reaction process of Ni and O in the AlGaN barrier may be related to the formation of deep states.…”
Section: Resultsmentioning
confidence: 99%
“…These ions would be attracted to negatively charged threading dislocations due to their trapping of electrons [27], this could change their electrical conductivity and hence the vertical conductivity in the surface epitaxy. An alternative picture would be diffusion of nitrogen out of the epitaxy, it has been shown that nitrogen can diffuse from the surface leaving vacancies which increase leakage [28]. Future work should investigate the mechanism for this observed increase in vertical conductivity in these devices .…”
Section: F Suggestions For a Physical Mechanismmentioning
confidence: 99%
“…A GaN layer after growth naturally contains many defects near the surface. 3,9,44 These defects tend to generate electronic surface levels that capture carriers, resulting in nonradiative recombination and degradation of the light emitting efficiency. Through oxidation, these defects could have been consumed into the oxide layer: namely, defects near the surface could be reduced by oxidation.…”
Section: Surface Passivation Effectsmentioning
confidence: 99%
“…In dry etching, for example, these high energies are usually supplied by accelerated ions or plasma-assisted species. Dry processes, however, use highenergy reactions with plasma or high-temperature conditions and thus tend to generate surface damage and defects ͑V N ͒, 8,9 leading to high-density surface states, formation of shallow donor levels, 10,11 and large leakage currents. 9,12 These surface electronic states can capture carriers, causing to unintentional surface charge up, nonradiative recombination, and Fermi-level pinning, thus affecting device characteristics.…”
Section: Introductionmentioning
confidence: 99%